An Application Of Satisfaction Assessment Of Community Services In Padang Lebar Village Office Using The Oreste Method - Pandita Juwinarti; Asnawati Asnawati; Reno Supardi (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
The process of assessing community satisfaction in Padang Lebar Village Office manually is by using a questionnaire, therefore an application was made to facilitate the assessment of satisfaction with these community services. The application for assessing satisfaction with community services is an application used to assess community satisfaction with the services provided by employees of Padang Lebar Village Office. The research method used is the Oreste Method, which is a multi-criteria decision making method or better known as Multi Criteria Decision Making (MCDM). MCDM is used to solve problems with conflicting criteria to be able to make a decision to reach a final decision. The result of this research is a software that adopts the Oreste method which is able to help Padang Lebar Village Office for decision making in determining the level of service satisfaction to the community every year. This application for assessing satisfaction with community services can help the management of Padang Lebar Village Office in assessing the performance of village employees. The Writer suggests that the application for assessing satisfaction with community services can be used to facilitate inputting data in assessing community satisfaction with existing services at the Padang Lebar Village Office.